A Tale of Two Cities: is Overvaluation a Capital Issue? - Muellbauer, J (Springer, 2019)
Empirical evidence on what drives house prices, such as income changes, extrapolative expectations and differences in supply elasticities, is important. In many countries, house price movements in major cities such as the capital are more extreme and often seem to lead the rest of the country. This chapter therefore proposes a framework for analysing prices at a regional level, with an application to London illustrating its leading role and the ripple effect in other UK regions. As is also shown for Paris, capital cities are more sensitive to interest rates and credit conditions, and international investors can play an important role (perhaps leading to affordability problems for local residents). After the crisis, debt-to-income ratios have risen strongly which, together with the higher interest rate sensitivity of housing in cities, may impede the normalisation of interest rates.